The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1002/1097-0142(19810415)47:8<2087::aid-cncr2820470830>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusion in breast cancer: A review of 105 cases

Abstract: This paper reviews 105 patients with breast cancer who had a pleural effusion as a direct consequence of metastatic disease. The mean lag time between diagnosis of primary tumor and presentation of the effusion was 41.5 months. Mean survival time after development of an effusion was 15.7 months. Of the 99 patients with unilateral breast tumors, 50% had ipsilateral effusions, 40% were contralateral, and 10% were bilateral. Forty-two percent of the patients had pleural effusion as the first evidence of recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0
2

Year Published

1982
1982
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 10 publications
4
42
0
2
Order By: Relevance
“…Breast cancer relapses in the form of serous malignant effusions for about one half of patients. 11,12 Clinical samples may be available from palliative treatment of breast cancer patients, allowing the characterization of metastatic cells in effusions. Recent studies have described genotypic 13 and phenotypic 14,15 alterations for some metastasis-associated and regulatory molecules in breast primary tumors and pleural effusions.…”
mentioning
confidence: 60%
“…Breast cancer relapses in the form of serous malignant effusions for about one half of patients. 11,12 Clinical samples may be available from palliative treatment of breast cancer patients, allowing the characterization of metastatic cells in effusions. Recent studies have described genotypic 13 and phenotypic 14,15 alterations for some metastasis-associated and regulatory molecules in breast primary tumors and pleural effusions.…”
mentioning
confidence: 60%
“…Among the patients with malignant Such variation might be attributed to the calendar year studied, the region of the country in which the patients were treated, the study methodology, or the population studied. Fentiman et al (8) found that the mean interval between the diagnosis of the primary tumor and the presentation of pleural effusion was 41.5 months, and that the mean survival after the presentation of pleural effusion was 15.7 months. However, van Galen et al (11) reported a longer mean time from the diagnosis of breast cancer to the detection of pleural effusion (63.6 months) and a shorter mean survival (9.3 months), findings that are in stark contrast with those of our study (20 months and 6 months, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the spread of breast cancer have shown that a longer interval free of pleural metastases is an indicator of a worse prognosis, (8,10,11) and this poor prognosis has been associated with factors such as the site of the metastasis and the identification of malignant cells in the pleural fluid (23) ; the expression of c-erbB-2 (21) ; the triple-negative phenotype (11,(15)(16)(17) ; and Ki-67 protein expression, which has been shown to be present in 63% of patients with malignant pleural effusion. (18,24,25) The worst breast cancer survival rates are in developing countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations